The Implementation of Tembang Macapat Learning as A Means of Primary School Character Education - Arfiki Rochadiana; Sabar Narimo; Yeny Prastiwi; Laili Etika Rahmawati (Journal of Innovation in Educational and Cultural Research, 2022)
Javanese culture has become unfamiliar to the millennial generation, even though character values in Javanese culture are excellent. Javanese culture is mainly introduced traditionally, one of which is the tembang macapat. The research aimed to describe character education, including planning, implementation, and evaluation in tembang macapat, which is taught in primary school, particularly in high grades, in grades four, five, and six. This research applied qualitative research with phenomenological methods. The data collection techniques used interviews, observation, and documentation. Triangulation was used to test the validity of the data. The data analysis techniques consisted of data collection, data reduction, data display, verification, and conclusion. Then it presented and concluded from the data that has been analyzed. The findings were as follows: 1) Planning for tembang macapat learning by analyzing the initial conditions of Primary School character education activities; 2) The tembang macapat learning was implemented once a week in the morning assembly and created tembang macapat poster; 3) Evaluations of tembang macapat learning instilled in students were the character of brotherhood, togetherness, affection, courtesy, respectfulness, and humility. Therefore, it concluded that the tembang macapat of gambuh, mijil, and dhandanggula can be used to strengthen primary school character education.